CSA: Thực hành nông nghiệp thông minh với khí hậu ở Việt Nam - Tan Yen, Bui; Thi Sen, Pham; Do, Trong Hieu; Ngoc Quyen, Luu; Viet Dung, Le; Thi Thanh Hai, Nguyen; Van Chinh, Nguyen; Khai Hoan, Le; Quang Thuong, Ha; Cao Anh Duong; Thi Hoa Sen, Le; Huu Cuong, Ho; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
During the last five years, Vietnam has been one of the countries most affected by climate change. Severe typhoons, flooding, cold spells, salinity intrusion, and drought have affected agriculture production across the country, from upland to lowland regions. Fortunately for Vietnam, continuous work in developing climate-smart agriculture has been occurring in research organizations and among innovative farmers and entrepreneurs. Application of various CSA practices and technologies to adapt to the impact of climate change in agriculture production have been expanding. However, there is a need to accelerate the scaling process of these practices and technologies in order to ensure growth of agriculture production and food security, increase income of farmers, make farming climate resilient, and contribute to global climate change mitigation. This book aims to provide basic information to researchers, managers, and technicians and extentionists at different levels on what CSA practices and technologies can be up scaled in different locations in Vietnam.